An Efficient Method for DNA Purification‐Free PCR from Plant Tissue. Issue 11 (8th November 2021) - Jia, Zhengnan; Han, Xiaowei; Tsuda, Kenichi
Abstract: Amplification of genomic DNA fragments by PCR is necessary for plant molecular biology approaches such as genotyping. While this is a routine molecular technique in a modern laboratory, there are still significant hurdles when analyzing a large number of samples or collecting and storing samples while in the field. Because PCR amplification directly from plant tissue is often unsuccessful due to various inhibitors, genomic DNA purification is usually required, which involves laborious and time‐consuming procedures or costly materials, particularly when using commercial kits. These undermine scalability and use in less‐equipped settings. In addition, plant tissues and purified DNA need to be stored under proper conditions to avoid degradation. Here, we describe a low‐cost, high‐throughput PCR method to amplify genomic DNA fragments from plant tissue pounded to cellulose‐based filter paper without the need for DNA purification or special equipment for sample storage. In this protocol, a small punch of plant tissue is pounded to a commercially available or homemade DNA storage card and directly placed into a PCR mixture containing Tween‐20, a non‐ionic detergent, directly followed by PCR. We also describe the steps to prepare a homemade DNA storage card, which is easy to make and can be stored with plant tissue at room temperature for a long time without any special equipment, allowing us to test the same sample multiple times. We have used this method in at least eleven plant species, including arabidopsis, tomato, soybean, potato, cotton, and rice. Altogether, our method decreases labor and cost, thereby increasing throughput and making plant DNA‐based molecular diagnostic assays accessible to resource‐limited settings, including classrooms, and facilitating sample collection in the field. © 2021 Wiley Periodicals LLC. Basic Protocol 1 : Making a homemade cellulose‐based DNA storage card Basic Protocol 2 : Pounding plant tissue on a DNA storage card Basic Protocol 3 : DNA‐purification free PCR